COMMUNICATION STRATEGY TO INCREASE ACHIEVEMENT INDONESIAN TAEKWONDO ATHLETES - Atmanegara, Reinaldy; Zulfiningrum, Rahmawati (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2023)
Taekwondo trainers have indirectly become role models for athletes, their habits, methods, traits and motivation in training greatly determine the character and success of athletes, effective and efficient two-way communication is an important factor that coaches must master. The role of the trainer is also important in the Indonesian Taekwondo National Training Center so that it can improve the quality and achievement of Indonesian Taekwondo National Training athletes. This study uses a descriptive method with a qualitative approach with interviews with key objects, namely athletes and coaches of the Indonesian Taekwondo National Training Center. The results of this study are that the trainers of the National Taekwondo National Training Center apply persuasive communication strategies to athletes to form good personal relationships between coaches and athletes. Coaches and athletes must have effective communication skills in order to help each other in solving a problem and provide mutual support. In a process of forming effective communication, support from both parties must be well established. Inhibiting factors that affect communication are the athlete's self-problems, facilities, lack of interaction from junior athletes. Supporting factors are openness, motivation, discipline and support.